The Globalisation of Indian Economy: The Impact of Globalization on the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Globalization (or globalization) describes a process by which regional economies, societies, and cultures have become integrated through a global network of communication, transportation, and trade. The term is sometimes used to refer specifically to economic globalization the integration of national economies into the international economy through trade, foreign direct investment, capital flows, migration, and the spread of technology. Globalization as a spatial integration in the sphere of social relations when he said “Globalization can be defined as the intensification of worldwide social relations which link distant locations in such a way that local happenings are shaped by events occurring many miles away and vice – versa.” Globalization generally means integrating economy of our nation with the world economy. The economic changes initiated have had a dramatic effect on the overall growth of the economy. It also heralded the integration of the Indian economy into the global economy. The Indian economy was in major crisis in 1991 when foreign currency reserves went down to 1 billion. Globalization had its impact on various sectors including Agricultural, Industrial, Financial, Health sector and many others. It was only after the LPG policy i.e. Liberalization, Privatization and Globalization launched by the then Finance Minister Man Mohan Singh that India saw its development in various sectors.